Sosialisasi Dan Pembuatan Alat Komposter Sebagai Upaya Pengelolahan Limbah Organik Rumah Tangga Di Desa Bareng, Kecamatan Bareng, Kabupaten Jombang (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Waste management is one thing that needs to be of concern to the community. Waste management is carried out as an effort so that waste does not pollute the environment and can be utilized so that it functions. Waste management in the community can be done through making compost that can be reused by the community. The goal of the composting process is to convert organic matter from household waste into compost that can be safely applied to fields without causing negative effects to either the soil or domesticated plants. The results of this compost are solid or liquid. Procurement of composters was carried out for the community in all hamlets of Bareng Village, Bareng District, Jombang Regency, East Java, by holding socialization and composting practices to provide education to all Bareng Village residents located at the Village Hall. Procurement of composters is carried out as an effort to increase knowledge about waste management through composters, so that people can make the most of household waste.